2000
DOI: 10.1109/10.827308
|View full text |Cite
|
Sign up to set email alerts
|

Variability in EMF permittivity values: implications for SAR calculations

Abstract: Digital anatomical models of man and animals are available for use in numerical calculations to predict electromagnetic field (EMF)-induced specific absorption rate (SAR) values. To use these models, permittivity values are assigned to the various tissues for the EMF frequencies of interest. There is, as yet, no consensus on what are the best permittivity data. This study analyzed the variability in published permittivity data and investigated the effects of permittivity values that are proportional on SAR cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 9 publications
1
37
0
Order By: Relevance
“…Recently, Hurt et al [2000] reported on the permittivity values of biological tissues published elsewhere in literature that deviate substantially from the data published by Gabriel. The ratios that re¯ect the unchanged differences among published data were calculated.…”
Section: Introductionmentioning
confidence: 71%
“…Recently, Hurt et al [2000] reported on the permittivity values of biological tissues published elsewhere in literature that deviate substantially from the data published by Gabriel. The ratios that re¯ect the unchanged differences among published data were calculated.…”
Section: Introductionmentioning
confidence: 71%
“…The choice of complex permittivity values is not a definitive one because of the uncertainty that exists in the literature on the dielectric properties of normal breast tissue at microwave frequencies [17]. Three dielectric spectroscopy studies [18]- [20] suggest that normal breast tissue is a low-dielectric-constant, low-loss material and that the within-patient variability in dielectric properties is less than 10% around the nominal values.…”
Section: B Em Modelmentioning
confidence: 99%
“…The dielectric properties are defined in terms of relative permittivity and conductivity , and their numerical values for the simulations are described in Table 2. The absorption is well-known to depend more on conductivity than on relative permittivity; namely, as conductivity increases, the AL also increases [12,13].…”
Section: Resultsmentioning
confidence: 99%